Design of Traffic Control Solutions and Infrastructure Alignment to Overcome Congestion Problems in Batam City. - Siregar, Dian Sari; Mulia Pamadi (Journal of Civil Engineering and Planning (JCEP), 2024)
Batam City is one of the cities that experiences significant traffic congestion problems, especially around the Traffic Light intersection. This research aims to identify and analyze the factors that influence the smoothness of traffic at the Batam City Traffic Light Intersection, as well as designing integrated solutions to overcome these problems. Through study stages involving data collection, analysis of key factors causing traffic jams, and modeling the impact of each factor, this research tries to provide recommendations for improving infrastructure, redesigning intersections, using traffic light technology, and providing education to motorists. It is hoped that the results of this research can serve as a guide for the government and stakeholders in improving traffic management and quality of life in Batam City.